Core participant marking in Khumi - Peterson, David A. (2024)
In Bangladesh Khumi, core participants (S, A, P, and R) frequently occur with three apparent case markers: =lö1, =mö3, and =a1. Examination of these elements’ distribution in a large naturalistic text corpus, however, reveals the first two have primarily discourse motivations. =lö1 is a straightforward topic marker. =mö3 , which occurs mainly with A participants, would appear to be an ergative marker, but its distribution is much wider than A, including obliques, adverbials, and even P and S; it is concluded that it has more of a foregrounding function, including some types of focussing. =a1 is simply an extension of a general Kuki Chin locative marker, used mostly with animate Ps, but consideration of discourse data shows that use or omission of it may subtly manipulate the individuation of both animate and inanimate Ps.